Determination of gelatin from marshmallows using a combination of fourier transform infrared (ATR-FTIR) spectroscopic and chemometrics for halal authentication - Fatmawati, Sofia; Hariyanti, Hariyanti; Permanasari, Etin Diah; Chandra, Ady; Firmanto, Johan Dwi; Sari, Retno Lia; Pamungkas, Septiana Tri (Journal of Halal Science and Research, 2024)
Marshmallow is a foam that contains aerated sugar, which is stabilized with gelatin or egg albumin. In this research, a Fourier Transform Infra-Red (ATR-FTIR) spectroscopy combined with the Chemometrics methods is developed to distinguish the presence of porcine gelatin in marshmallows, which can then be used to identify halal products. This method provides fast and rapid testing of halal products. Marshmallows were made with varying concentrations of bovine and porcine gelatine as the reference. Commercial marshmallows were collected in the online marketplace by purposive sampling. Isolated gelatin was analyzed using the ATR-FTIR spectrophotometer, and data analysis was continued using PCA (Principal Component Analysis). The results showed that bovine gelatin absorbed at a wavenumber of 1638 cm-1, while porcine gelatin produced a sharp absorption at 1697 and 1654 cm-1. The results of PCA analysis show that 100% of bovine gelatin marshmallows (S100) have areas different from marshmallows containing a mixture of porcine gelatin. The PCA results of four samples (A1, A2, A3, and A4) show they are in the same area as 100% bovine gelatin marshmallows (S100). This shows that it is suspected that the four marshmallow samples tested did not contain porcine gelatin. The multivariate regression curve showed that the pattern of linear absorbance changes along with porcine gelatin concentrations with the highest coefficient equation is from wavenumber 1093.97 cm-1.   Keywords: ATR-FTIR, Bovine gelatin, Chemometric, Marshmallow, Porcine gelatin